Toxicity of Carlina Oxide—A Natural Polyacetylene from the Carlina acaulis Roots—In Vitro and in Vivo Study - Wnorowski, Artur (Toxins (Basel), 2020)
There are several reports indicating that the roots of the Carlina acaulis L. used to be commonly applied as a treatment measure in skin diseases and as an antiparasitic agent, starting from antiquity to the 19th century; however, nowadays, it has lost its importance. Currently, numerous studies are being conducted assessing the possibility of reintroducing C. acaulis-derived extracts to phytotherapy. Determining the safety profile of the main constituents of the plant material is crucial for achieving this goal. Here, we aimed to determine the toxicity profile of carlina oxide, one of the most abundant components of the C. acaulis root extract. We obtained the carlina oxide by distillation of C. acaulis roots in the Deryng apparatus. The purity of the standard was evaluated using GC-MS, and the identity was confirmed by IR, Raman, and NMR spectroscopy. In vitro cytotoxicity was assessed using a panel of human cell lines of skin origin, including BJ normal fibroblasts and UACC-903, UACC-647, and C32 melanoma cells. This was accompanied by an in vivo zebrafish acute toxicity test (ZFET). In vitro studies showed a toxic effect of carlina oxide, as demonstrated by an induction of apoptosis and necrosis in both normal and melanoma cells. Decreased expression of AKT kinase and extracellular signal-regulated kinase 1/2 (ERK1/2) was noted in the UACC-647 melanoma cell line. It was also observed that carlina oxide modified the expression of programmed cell death-ligand 1 (PD-L1) in tested cell lines. Carlina oxide exhibited high in vivo toxicity, with LC(50) = 10.13 µg/mL upon the 96 h of exposure in the ZFET test. Here, we demonstrate that carlina oxide displays toxic effects to cells in culture and to living organisms. The data indicate that C. acaulis-based extracts considered for therapeutic use should be completely deprived of carlina oxide.